Mechanical performance of asphaltic concrete incorporating untreated and treated waste cooking oil - Wan Azahar, Wan Nur Aifa; Putra Jaya, Ramadhansyah; Hainin, Mohd Rosli; Bujang, Mastura; Ngadi, Norzita (Elsevier, 2017)
In recent years, various oil-based modifications that involve the use of waste cooking oil (WCO) have been applied to deliver obvious benefits to the pavement industry. This effort is in line with the response to the issue of waste management. The current constraint in dealing with WCO is its declining rutting resistance performance at high temperatures. This issue is observed globally and remains unresolved. Adverse rheological performance induces the rutting issue due to the high susceptibility of WCO toward temperature exposure. The pretreatment of WCO is proposed as an extensive research work that aims to produce treated WCO before its addition to HMA. However, the potential of treated WCO is still at the empirical stage and still questionable. Therefore, a mechanical test was performed on the control, 5% untreated WCO, and 5% treated WCO mixtures to evaluate any improvement in the performance of the HMA incorporated with untreated and treated WCO. The mechanical test included the Marshall Stability, resilient modulus, creep stiffness, and indirect tensile strength (ITS) tests. Microstructure observation was performed using an atomic force microscope (AFM) to identify the surface roughness related to the adhesion properties. Results shows an improvement in Marshall Stability, resilient modulus, and ITS performance was recorded with the replacement of 5% treated WCO in bituminous mixture. In addition, the highest creep stiffness, with an enhancement of about 25% relative to the control mixture, was achieved with the 5% treated WCO mixture to resist permanent deformation. The microstructure observation revealed that the lowest surface roughness produced with the treated WCO in modified binder contributed to the improvement of adhesion bonding that increased the strength of the asphalt mixture.